Relationship Between Arm Muscle Strength and Overhand Service Performance Among Male Volleyball Athletes - M. Nusri Rachman (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aimed to determine the relationship between arm muscle strength and overhand volleyball service performance among male volleyball athletes of Padang Pariaman Family Association Pekanbaru. The study focused on examining the extent to which arm muscle strength contributes to the success of overhand service execution in volleyball. Methodology: This study employed a quantitative correlational research design. The population consisted of 16 male volleyball athletes of Padang Pariaman Family Association Pekanbaru, and total sampling was applied. Data were collected using a push-up test to measure arm muscle strength and an overhand service test to assess volleyball service performance. Data analysis included the Chi-Square normality test, Pearson Product Moment correlation analysis, t-test, and coefficient of determination analysis. Main Findings: The findings indicated a significant positive relationship between arm muscle strength and overhand volleyball service performance. The Pearson correlation coefficient was 0.619, exceeding the critical value of 0.497 at the 5% significance level. Furthermore, arm muscle strength contributed 38.31% to overhand service performance. Novelty/Originality of this study: This study provides empirical evidence regarding the contribution of arm muscle strength to overhand volleyball service performance among club-level athletes. Unlike previous studies that examined student populations or multiple physical components simultaneously, this research specifically quantifies the relationship and contribution of arm muscle strength to service performance in competitive volleyball athletes, offering practical insights for strength-based training program development.